Preliminary ships' trials of chlorinated rubber antifouling paints - Rascio, Vicente J. D. (1981)
Up to now, antifouling paints have been the most adequate method of controlling the settlement of organísms on ships'hulls. In practice, their main drawback is the loss of toxicant that takes place during navigation and which does not have an effective action on foulinq, as this adheres only when the ship is anchored in port or when it naviqates at speeds below A-5 knots. For this reason it has not been possible so far to obtain products whose effectiveness endures for periods of more than two or three years. This protection period is shorter than that of modern anticorrosive painting systems for the underwater part of the hull. The enlargement of the intervals between drydockings and the maintaining of vessels free from corrosión and fouling pro- blems are the current targets of technological research in this subject. In previous stages the authors have developed antifouling formulations of the oleoresinous type of high toxicity. They were determined by means of tests on ships and experimental rafts. The studies currently underway are aimed to obtain antifouling paints based on a chlorinated rubber binder, which show not only great effectiveness and bioactivity, but also excellent adhesion on marine anticorrosive primers prepared with different pigments. Chlorinated rubber resin is being now used in the paint industry particularly, because the film, when correctly plasticized, has excellent resistance to Chemical agents, the paints are easy to apply and the film dries quickly. In the case of anticorrosive formulations, chlorinated rubber paints provide an excellent barrier effect against water and oxygen.